P08 Cancer of oesophagus or gastricus—new assessment of technology of endosonography: findings. (16th November 2010) - Russell, I; Attwood, S; Barr, H; Edwards, R Tudor; Gliddon, A; Ingledew, D; Park, K; Russell, D; Yeo, S T; Whitaker, R
Abstract : Objectives: Endoscopic ultrasound (EUS) is recommended for staging gastro-oesophageal cancers but has never been rigorously evaluated. This trial assessed whether EUS, when added to usual staging tests: changes treatment; improves survival and quality of life; and uses resources cost-effectively. Methods: We conducted a pragmatic randomised trial in eight centres. As 80% of participants came from two centres, we combined the other centres for analysis. Patients diagnosed with gastro-oesophageal cancer received a standard staging protocol, after which the multi-disciplinary team agreed a provisional management plan. In principle the choice lay between endoscopic mucosal resection, immediate surgery, neoadjuvant chemotherapy followed by surgery, or multi-modal treatment (ie chemotherapy and radiotherapy). We then randomised consenting patients without metastases by telephone to receive EUS or not. Thereafter we recorded changes in the management plan, in the use of healthcare resources and in participant-reported outcomes. In particular we focused on three facets of quality of life: generic (measured by the EQ5D), cancer-related (FACT general scale and subscales) and condition-specific (FACT additional concerns scale). We then followed participants at defined intervals till the end of the trial—that is for between one and 3.5 years. Findings: We randomised 223 patients, of whom 213 yielded enough data for primary analysis. At the end of the trial 45% of EUS participants and 32% of the non-EUS participants were alive. EUS improved survival adjusted for generic quality of life with an HR of 0.69 (95% CI 0.49 to 0.98); and both its components—survival and EQ5D scores; the benefits of EUS were significantly greater for those with poor initial quality of life, but there was no difference between centres. Similarly, there was a significant interaction between initial quality of life and the effect of EUS on all the FACT scales; again sicker patients benefitted more from EUS. However, there was no significant difference between EUS and non-EUS groups in mean FACT scores adjusted for covariates. Both management plans and final treatment varied between centres. Although EUS changed the management plan for several participants, differences between groups in actual treatment and the proportion of tumours completely resected were not significant. In both groups, two thirds of initial treatment plans were for chemotherapy followed by surgery, but 40% of participants received multi-modal or palliative treatment. Conclusion: EUS has a beneficial effect on survival and generic quality of life, especially for participants initially in poorer health.